Cause-related marketing: Led corporate social responsibility in international business-to-business markets: the contingent roles of host-country sustainable development. Issue 4 (25th September 2019) - Liu, Gordon; Wu, Meng-Shan Sharon; Ko, Wai Wai; Chen, Cheng-Hao Steve; Chen, Yantai
Abstract : Purpose: Cause-related marketing (CRM) focuses on the use of marketing tools to publicize a firm's corporate social responsibility (CSR) activities. Drawing on legitimacy theory, the purpose of this paper is to investigate the impact of CRM-led CSR in international business-to-business (B2B) markets. In particular, the authors examine the relationship between supplier CRM-led philanthropic CSR reputation and foreign customer business engagement in an international B2B setting. The authors also test how the foreign customer's host-country sustainable development level moderates this relationship. Design/methodology/approach: The authors collect and analyze dyadic data from multiple sources including: dyadic data from a supplier and its 90 foreign customers; the supplier's internal company records; and publically available data. Findings: The authors find that supplier CRM-led philanthropic CSR reputation positively affects foreign customer business engagement. Furthermore, the authors find that this positive relationship is stronger when host-country environments are characterized by achieving higher level of environmental well-being development. In contrast, this positive relationship is weaker when the foreign customer host-country environment is characterized by achieving higher level of economic well-being development. Originality/value: The authors examine that impacts of CRM-led CSR in international B2B markets and differentiate the contingent roles of foreign customer host-country sustainable development in moderating such impacts.